IDENTIFIKASI AKUIFER DI DAERAH RAWAN BANJIR DENGAN METODE VERTICAL ELECTRICAL SOUNDING DI KECAMATAN MUARA BANGKAHULU (Identification of Aquifers in Flood-Prone Areas using the Vertical Electrical Sounding Method in Muara Bangkahulu sub-district) - Suhendra; Geri Budianto; Halauddin; Liza Lidiawati (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2023)
Muara Bangkahulu Subdistrict is a flood-prone area in Bengkulu City, Bengkulu Province. This study aims to identify the depth of aquifers in flood-prone areas. Flood-prone areas in the Muara Bangkahulu sub-district were analyzed using the Vertical Electrical Sounding (VES) method with Schlumberger configuration of as many as 40 VES points in residential areas. Data acquisition was carried out using the Geoelectric IP Meter MAE X612-EM. The obtained data was then processed using Progress 3.0 software to get a 1D Resistivity Log cross-section. The log data was then modelled using Voxler 4 software to find an overview of the distribution of aquifers and subsurface structures in 3D. The distribution of resistivity values at depths of 2, 5, 10, 15, 30, and 40 meters using ArcGIS 10.8 are mapped to see the distribution of aquifers. The aquifers in the Muara Bangkahulu sub-district are sand and gravel with a value of 0-25 Ω.m. The intrusion of seawater influences this value. Flood-prone areas are located at shallow aquifer, namely depths of 2-5 m in the villages of Rawa Makmur, Rawamakmur Permai, and Bentiring Permai.